Temporal trend and factors associated with spatial distribution of congenital syphilis in Brazil: An ecological study - Dantas, Janmilli da Costa; Marinho, Cristiane da Silva Ramos; Pinheiro, Yago Tavares; Ferreira, Maria Ângela Fernandes; da Silva, Richardson Augusto Rosendo (Frontiers in Pediatrics, 2023)
Objective The study aimed to analyze the temporal trend of congenital syphilis in Brazil in the period from 2008 to 2018 and its spatial distribution in the Immediate Regions of Urban Articulation, and to identify spatial correlations with socioeconomic factors and prenatal care. Methods Spatial correlations between the incidence of congenital syphilis and socioeconomic conditions and access to prenatal care were assessed. This ecological study conducted a time series analysis in Brazil and spatial analysis in 482 Immediate Regions of Urban Articulation. Cases of congenital syphilis reported in the Notifiable Diseases Information System and the Live Birth Information System from January 1, 2008, to December 31, 2018 were included. Socioeconomic conditions (percentage of individuals with inadequate water supply and sanitation) were extracted from the 2010 census, whereas the Live Birth Information System provided data on access to prenatal care (percentage of live births with 1–3 prenatal care appointments). The Joinpoint Regression software performed the temporal trend analysis, while the GeoDa software assessed territorial clusters using the Moran’s I and Local Spatial Association Indicator. Results The incidence of congenital syphilis showed an upward trend (annual percent change 1 = 26.96; 95% CI: 18.2–36.3; annual percent change 2 = 10.25; 95% CI: 2.7–28.4) and was unevenly distributed across Immediate Regions of Urban Articulation in Brazil (Moran’s I = 0.264, p ≤ 0.05). It also presented a direct spatial correlation with the percentage of individuals with inadequate water supply and sanitation (Moran’s I = 0.02, p ≤ 0.05) and the percentage of live births with 1–3 prenatal care appointments (Moran’s I = 0.03, p ≤ 0.05). Conclusion Agrowth trend of congenital syphilis in Brazil was observed between 2008 and 2018. Moreover, inequalities in socioeconomic conditions and access to prenatal care influenced the spatial distribution of this disease.